Optimalisasi Manajemen Waktu dan Sumber Daya dalam Pelatihan Kesenian Habsy di SDIT Al-Qonita Melalui Program Penguatan Profil Pelajar Pancasila (P5) - Abrar, Muhammad; Sulistyowati, Sulistyowati (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Habsy's arts training at SDIT Al-Qonita faced challenges in time management and the diversity of students' levels of understanding of the tempo of music and poetry. To overcome this, the Pancasila Student Profile Strengthening Program (P5) approach was implemented to integrate training into project-based learning that is oriented towards character development and Islamic values. This research aims to optimize time and resource management in Habsy training while preserving Islamic traditions. This research uses a service learning method that combines technical learning with service experience, where students not only learn to play musical instruments and recite Islamic poetry, but are also involved in technical preparation and weekly reflection. The research results show that resource optimization is the key in this training. In-house teachers and professional trainers work together to maximize students' potential, while training facilities, such as musical instruments and practice rooms, are utilized efficiently. Structured timings help overcome time management challenges, ensuring each training session is effective. This training not only improves students' technical skills but also strengthens character values ​​such as cooperation, responsibility and appreciation for Islamic art. The P5 arts performance is the pinnacle of the program's success and has a positive impact on students..